2013
DOI: 10.1075/jicb.1.1.03may
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous immersion education

Abstract: This article outlines key developments internationally over the last 40 years in indigenous immersion education. Most notable here has been the establishment of community-based, bottom-up immersion programs, instigated by indigenous communities with the aim of maintaining or revitalizing their indigenous languages. As such, the article addresses a relative lacuna in immersion education literature, which has to date focused primarily on second-and foreign-language contexts. The article first provides a wider so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Drop out or "push out" rates, low scores on standardized achievement tests, tests of motivation and cultural pride, and numerous other reports indicate this failure (May, 2013). In response to this failure, indigenous immersion schooling has been a key strategy for revitalization, and a response to failed colonial schooling.…”
Section: Impact Of Colonialism and Indigenous Language Revitalizationmentioning
confidence: 97%
See 3 more Smart Citations
“…Drop out or "push out" rates, low scores on standardized achievement tests, tests of motivation and cultural pride, and numerous other reports indicate this failure (May, 2013). In response to this failure, indigenous immersion schooling has been a key strategy for revitalization, and a response to failed colonial schooling.…”
Section: Impact Of Colonialism and Indigenous Language Revitalizationmentioning
confidence: 97%
“…We propose that through our research and experience, we have observed identity as a driving force for models of immersion we see in indigenous communities. Some suggest postcolonial political dynamics, especially internalized oppression, 1 present the biggest ideological and emotional challenges to successful immersion programs (Bishop, Berryman & Richardson, 2002;Hermes, 2007;Johnston, 2002;May, 2013;Warner, 1999;Wilson & Kamanā, 2011).…”
Section: Indigenous Identity Developmentmentioning
confidence: 98%
See 2 more Smart Citations
“…However, as May (2013) points out, translating language policy into effective pedagogy and practice is not straightforward. Our investigation of the everyday experiences of three-to five-year olds in GM preschool settings raised questions about the quality of the learning opportunities they encountered and the appropriateness of the pedagogic practices we observed.…”
Section: Introductionmentioning
confidence: 99%